PRESERVATION OF ROTTERDAM FORT POST BONGAYA AGREEMENT IN MAKASSAR - Fadilah, Nurul; Dahlan, M.; Syukur, Syamzan (Program Pascasarjana, UIN Alauddin Makassar, 2021)
The purpose of this study was to clear analyze the existence of Fort Rotterdam and its preservation after the Bongaya agreement in Makassar. This study uses the steps in writing history, namely heuristics, criticism, interpretation and becomes a historiographical work with the literature study method. The results of this study indicate that First, Ujung Pandang Fortress have built by the Kingdom of Gowa to defend the greatness and dignity of the Gowa kingdom from colonial threats. This fort is one of the guard forts of the main fortress of Somba Opu, which is the center of the Kingdom of Gowa. After the Gowa kingdom lost the Makassar war and confirmed by the Bongaya Agreement on 18 November 1667, the Ujung Pandang fort fell into the hands of the VOC (Netherlands Indies Trade Association) and changed its name to Fort Rotterdam and as a spice-trading center from east to west. Second, the preservation of the fort after the Bongaya Agreement, namely during the Japanese occupation. The fort have used as a center for language and agricultural research activities, after that in 1973 after independence the fort changed its function as the National Institute of Antiquities and Heritage, which is currently known as the Cultural Heritage Conservation Center and Museum La Galigo.